1991
DOI: 10.2105/ajph.81.10.1313
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of national reporting of communicable diseases: the experience of the National Electronic Telecommunications System for Surveillance.

Abstract: The timeliness of reporting four nationally notifiable diseases was examined using data reported via the National Electronic Telecommunications System for Surveillance. Timeliness of reporting varied by disease (bacterial meningitis: median 20 days; salmonellosis: median 22 days; shigellosis: median 23 days; and hepatitis A: median 33 days) and by state. These findings indicate a need to standardize surveillance definitions and to account for reporting differences between states in interpreting regional diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 8 publications
0
25
2
Order By: Relevance
“…However, since there should not be a longer delay between the onset date and the date of sample collection, one could conclude that the timeliness in the reporting has improved since then. Also studies from other countries have shown that meningococcal infection, measles and/or salmonellosis were reported most rapidly, while TB and other mycobacteria had the longest delays (8,9,11,14,15,18,19). The conclusion drawn from all these studies is that differences in the delays between diseases seem to be dependent on the level of urgency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, since there should not be a longer delay between the onset date and the date of sample collection, one could conclude that the timeliness in the reporting has improved since then. Also studies from other countries have shown that meningococcal infection, measles and/or salmonellosis were reported most rapidly, while TB and other mycobacteria had the longest delays (8,9,11,14,15,18,19). The conclusion drawn from all these studies is that differences in the delays between diseases seem to be dependent on the level of urgency.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that efficient electronic reporting systems are expected to produce higher quality because less time is needed to write, file and transmit notifications (17,18). The easiest way of increasing the performance is thus to design a modern electronic surveillance system eliminating any unnecessary delay in the flow due to handling and sending papers.…”
Section: Discussionmentioning
confidence: 99%
“…Passive surveillance is often associated with delayed and low reporting [29][30][31]. Because measles is highly contagious and the virus is particularly communicable during catarrhal stage (about 7 days post exposure or 3 days before onset of rash) [32], an index case may cause two further generations of cases by the fourth day after onset of rash.…”
Section: Discussionmentioning
confidence: 99%
“…There are 61 reportable dis¬ eases under state jurisdiction. Further, 15 tion of the SHD, 30 require confirmation and correlation with specimens submitted to an ap¬ proved laboratory, and 28 require supplemen¬ tal forms to be filled out and sent to the SHD.…”
Section: Effectiveness Of Electronic Communication and Technology Issuesmentioning
confidence: 99%
“…The SHDs send the report for the entire state the same week that the data are received from the local CHDs. However, the delay between the onset of a disease and e-mail reporting by the SHD to the CDC can vary, as epidemic-prone diseases that require laboratory confirmation have longer reporting delays 15. …”
mentioning
confidence: 99%